2014
DOI: 10.5301/ejo.5000444
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy and Safety of the Ophthalmic Insert Mydriasert in Patients Undergoing Retinal Angiography

Abstract: Mydriasert assures an adequate degree of mydriasis for retinal angiography in both diabetic and nondiabetic patients. There are no differences in efficacy or safety between the insert and the usually administered eyedrops, but the low total drug dose administered with the insert reduces the risk of cardiovascular side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…14,18 Dilation was more stable with the mydriatic ophthalmic insert; at 90 minutes, the pupil diameter was larger in the insert group than in the eyedrops group. 73,74 Other Outcomes The mean number of nurse interventions to reach effective dilation was consistently lower in mydriatic ophthalmic insert groups than in mydriatic eyedrops groups. 6,18 The mean operative time was short and comparable in both groups.…”
Section: Comparative Studies Of the Mydriatic Ophthalmic Insert And Mmentioning
confidence: 98%
See 2 more Smart Citations
“…14,18 Dilation was more stable with the mydriatic ophthalmic insert; at 90 minutes, the pupil diameter was larger in the insert group than in the eyedrops group. 73,74 Other Outcomes The mean number of nurse interventions to reach effective dilation was consistently lower in mydriatic ophthalmic insert groups than in mydriatic eyedrops groups. 6,18 The mean operative time was short and comparable in both groups.…”
Section: Comparative Studies Of the Mydriatic Ophthalmic Insert And Mmentioning
confidence: 98%
“…14 There were no concerns for or significant between-group differences in blood pressure and heart rate. 18,[70][71][72][73] Only 1 study found an increased incidence of high systolic Figure 1. Comparative studies of mydriatic ophthalmic insert and mydriatic eyedrops (* Z first author; AE Z adverse effect; BP Z blood pressure; CNVA Z corrected near visual acuity; DBP Z diastolic blood pressure; HR Z heart rate; ICM Z intracameral mydriatics; MED Z mydriatic eyedrops; MOI Z mydriatic ophthalmic insert; NS Z not significant; Phenyl Z phenylephrine; SBP Z systolic blood pressure; SPK Z superficial punctate keratitis; Tropic Z tropicamide).…”
Section: Comparative Studies Of the Mydriatic Ophthalmic Insert And Mmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when compared to topical mydriatic eye drops, there was no significant difference in pupil dilatation. In addition, topical mydriatic eye drops dilate the pupil faster (within 15 min) compared to the Mydriasert ® insert (Cagini et al, 2014;Torron et al, 2013). The economic benefits of Mydriasert ® were investigated in a cohort of 1763 patients in the U.K.…”
Section: Rod-shaped Conjunctival Devicesmentioning
confidence: 99%
“…The second strategy is based on the administration of a solid insert of phenylephrine and tropicamide (Mydriasert ® ) [9]. The insert is an osmotic tablet, placed in the lower conjunctival bag by a trained medical staff and must remain for 30 to 45 min to induce a sufficient mydriasis, causing some discomfort for the patient [10].…”
Section: Introductionmentioning
confidence: 99%